2003
DOI: 10.1136/pmj.79.932.345
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous pneumothorax: use of aspiration and outcomes of management by respiratory and general physicians

Abstract: Background: Spontaneous pneumothorax is a common problem in hospital practice. Despite the publication of guidelines controversy over its initial management still exists, particularly over the use of simple aspiration. Methods: The management of spontaneous pneumothorax by respiratory and general physicians at our hospital was analysed by retrospective case note review. Eighty five patients were identified over the study period (36 managed by respiratory and 49 by general physicians).Results: There was a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Only 27 patients who had undergone simple aspiration were studied, and the authors conceded that statistical power was insufficient to formally confirm therapeutic equality. Similarly, most other previous studies or series were small, each including only around 30 -40 patients or less who had undergone the procedure (17,18,(22)(23)(24)(25)(26)(27). Andrivet and colleagues published a study involving a total of 68 patients in two protocols (28).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Only 27 patients who had undergone simple aspiration were studied, and the authors conceded that statistical power was insufficient to formally confirm therapeutic equality. Similarly, most other previous studies or series were small, each including only around 30 -40 patients or less who had undergone the procedure (17,18,(22)(23)(24)(25)(26)(27). Andrivet and colleagues published a study involving a total of 68 patients in two protocols (28).…”
Section: Discussionmentioning
confidence: 98%
“…The reported success rate of simple aspiration of spontaneous pneumothorax ranged from 34% to 93% (17,18,(22)(23)(24)(25)(26)(27)(28). This wide variation may be due to differences in the characteristics of included patients, differences in the definition of success, whether or not reaspiration was performed, and differences in the duration of follow-up.…”
Section: Success Ratementioning
confidence: 99%
See 1 more Smart Citation
“…The technique described in the guidelines, still practiced today, involved the use of a 16-gauge cannula under local anesthetic at the second intercostal space, mid-clavicular line, with a 50-mL syringe and a three-way tap (or stopcock). Compared to chest tube drainage, the advantages of simple aspiration are reduced hospital admission rate and reduced length of stay, translating into economic costsaving benefits (22,23). It is also a less painful procedure.…”
Section: Historical Perspectivementioning
confidence: 98%
“…The outcome of a treatment algorithm might also be influenced by the medical background of the treating physician. PACKHAM and JAISWAL [11], for instance, demonstrated that patients with PSP managed by respiratory physicians had, overall, fewer intercostal drains inserted and a significantly shorter length of hospital stay than those managed by nonrespiratory physicians.…”
mentioning
confidence: 99%